R- and G-band patterns in Astyanax scabripinnis paranae (Pisces, Characiformes, Characidae) - Maistro, Edson Luis [UNESP]; Foresti, Fausto [UNESP]; Oliveira, Claudio [UNESP] (Sociedade Brasileira de Genética, 1999)
A ausência de bandas longitudinais em cromossomos de peixes tem sido associada a problemas técnicos nas preparações cromossômicas ou à ausência de uma compartimentalização estrutural no genoma dos peixes. No presente estudo, um padrão de bandas R foi obtido usando a técnica de bandamento de replicação pelo tratamento in vivo com 5-BrdU. Padrões de bandamento G foram obtidos após tratamento dos cromossomos com tripsina e também após clivagem in situ com a endonuclease de restrição BamHI. Um padrão similar de bandamento G também foi obtido após clivagem dos cromossomos com a endonuclease HinfI. A presença de um resolutível padrão de bandamento R e G em Astyanax scabripinnis paranae mostra que seus cromossomos parecem apresentar estrutura isochore similar àquela encontrada em outros vertebrados.

The absence of longitudinal bands in fish chromosomes has been associated with technical problems in chromosome preparations or the absence of a structural compartmentalization in the fish genome. In the present study, a R-banding pattern was obtained using a replication banding technique by in vivo treatment with 5-bromodeoxyuridine (5-BrdU). G-banding patterns were obtained after trypsin treatment and also after chromosome cleavage by in situ treatment with the restriction endonuclease BamHI. A similar G-banding pattern was also obtained after cleavage with the endonuclease HinfI. Presence of a resolute R- and G-banding patterns shows that Astyanax scabripinnis paranae chromosomes could present an isochore-like structure similar to that found in other vertebrates.